Development Of Strategic Planning To Create An Effective School - Asep Saepul Hidayat; Ilma Srifa Nurmila (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
The development of strategic planning in the education system is urgent in creating effective schools, namely schools that have work processes that are consistent with the planning context. Meanwhile, strategic planning is planning that focuses on achieving the school's vision, mission and goals. In an effort to optimize strategic planning, sensitivity to changes in strategy is needed, respect for work risks, having a solid work team, creative, proactive, responsive to changes and problems, creative and innovative, and having high dedication to achieving goals according to targets, hopes and needs. , demands and ability adjustments. Therefore, the process of developing strategic planning includes 5 components that must be considered in school management, namely: (a) Strategy for achieving vision, mission and goals; (b) Strength of Planning Consistency; (c) Strengthening team collaboration; (4) Risk Management; and (5) the effectiveness of monitoring and evaluating the achievement of goals and the realization of effective schools.